An Integrated Access Structure and Encryption Scheme for Adequate Cloud Files: A Review - Gnanendra, Y; Basha, K. Thanweer (International Journal of Computer Sciences and Engineering, 2025)
Cipher textual content-coverage characteristic-based totally encryption (cp-abe) has been a desired encryption technology to clear up the difficult problem of comfy details sharing in CC. the shared information documents commonly has the function of multilevel hierarchy, mainly inside the place of healthcare and the military. But, the hierarchy shape of shared documents has been not explored in older systems. on this paper, a green record hierarchy function-based encryption concept is proposed in cloud computing. The layered get admission to structures are included into a unmarried right wing after which the hierarchical files are encrypted with the incorporated get right of entry to format. The cipher text additives associated with attributes may be shared thru way of the documents. Therefore, each cipher text storage and time charge of encryption is saved. Moreover, the proposed scheme is proved to be cozy under the equal vintage assumption. our experimental simulation indicates the proposed scheme that is quite in phrases of encryption and decryption